Implementasi Design Thinking dalam Perancangan UI/UX Rumah Sampah Digital Banjarejo - Yusril Febriyanto; Pristi Sukmasetya; Maimunah Maimunah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Garbage is a very serious problem, where the growth of waste is increasing day by day. Both the government and the public need to care about the waste itself, without any intervention from all of us, the waste problem will continue to grow and be difficult to overcome. For this reason, a waste bank was created which is expected to be able to reduce the rate of waste growth, as was done in the village of Banjarejo. But unfortunately the management of the waste bank in Banjarejo village had stopped. This is due to the lack of commitment from the waste bank management, and the decline in public trust and motivation to participate in the waste bank program. The purpose of this research is to revive the waste bank in Banjarejo village by digitizing the waste bank into the Banjarejo Digital Garbage House (RSDB). This research focuses on designing the web design of the Banjarejo Digital Garbage House (RSDB). The results of this study can later be tested on prospective users and waste bank admins in order to obtain test results. With the existence of the RSDB web system, it is hoped that it will be able to facilitate and foster the interest of the Banjarejo village community in efforts to clean the environment. This design uses the Design Thinking method. In the Design Thinking method there are 5 steps that must be carried out to get an idea and a solution, namely Empathize, Define, Ideate, Prototype, and Testing. Testing carried out on the prototype uses the Single Ease Question (SEQ). The results of the average SEQ score from the waste bank admin are 6.2 – 7. Meanwhile the average SEQ value results from the waste bank customers are 6 – 7. It can be concluded that the UI/UX on the RSDB prototype is easy to understand and according to user needs.